2000
DOI: 10.1046/j.1365-2516.2000.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimising local therapy during oral surgery in patients with von Willebrand disease: effective results from a retrospective analysis of 63 cases

Abstract: Bleeding after dental extractions is very frequent in patients with von Willebrand disease (vWD) and in the past often necessitated transfusions with factor VIII/von Willebrand factor concentrates (vWFc). To evaluate the benefits of a standard local therapy on bleeding complications during oral surgery, 63 consecutive patients with vWD were analysed retrospectively. All types of vWD were included: type 1 (n=31), type 2 (n=22) and type 3 (n=10). All the patients had dental extractions or periodontal surgery at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 21 publications
1
64
0
Order By: Relevance
“…Almost all parents of patients with VWD are willing to have their children circumcised. Short-term DDAVP prophylaxis was successfully applied ranging from 91% to 100% to prevent excessive bleeding following surgery or invasive procedures in patients with type 1 VWD [9,10]. In our study, clinical responses were excellent with no bleeding episode.…”
Section: Discussionmentioning
confidence: 49%
“…Almost all parents of patients with VWD are willing to have their children circumcised. Short-term DDAVP prophylaxis was successfully applied ranging from 91% to 100% to prevent excessive bleeding following surgery or invasive procedures in patients with type 1 VWD [9,10]. In our study, clinical responses were excellent with no bleeding episode.…”
Section: Discussionmentioning
confidence: 49%
“…In contrast, in the Nordic survey neither the FVIII:C levels nor the BT were routinely monitored in connection with surgery [13]. There are other groups who similarly found that at least during oral surgery the monitoring of FVIII/ VWF levels was probably not necessary [14].…”
Section: Discussionmentioning
confidence: 98%
“…Careful attention to hemostasis of an extraction socket and to suturing of sockets is also important in oral surgery in persons with vWD (grade C, level IV). 22 For fillings done under infiltration with local anesthetic, treatment with DDAVP or concentrates is not needed. Treatment should be given if an inferior dental block is to be used (grade C, level IV).…”
Section: -24mentioning
confidence: 99%